APLICAÇÃO DA MODELAGEM MATEMÁTICA EM UM SISTEMA DE SUSPENSÃO AUTOMOTIVA PASSIVA - Zago, Fernando; Locateli, Cristiano C.; Endler, Luciano; Rafikov, Marat; Valdiero, Antonio C. (Salão do Conhecimento, 2013)
Resumo